2014
DOI: 10.1111/jonm.12264
|View full text |Cite
|
Sign up to set email alerts
|

Professional behaviours and factors contributing to nursing professionalism among nurse managers

Abstract: Awareness of extrinsic professional factors is important continually to maintain nursing professionalism. The findings of our study may help nurse managers to continue their self-development and to realise the potential of their nursing staff by developing professionalism. These findings also provide an understanding of international professionalism trends to achieve higher levels of nursing professionalism through the evaluation of professional nursing behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 33 publications
3
44
0
2
Order By: Relevance
“…Previously published studies have not reached a consensus on gender differences in the perception of NP. Some studies have found that gender is not a predictor of NP (Tanaka, Taketomi, Yonemitsu, & Kawamoto, ; Wynd, ), whereas others have reported that male nurses or male nursing students tend to have higher NP, as in our study (Ko & Kim, ). Ko and Kim () interpreted this result as reasonable, as without a strong perception of NP, males might have found it difficult to choose nursing as a career, despite the social prejudice they would experience.…”
Section: Discussionsupporting
confidence: 42%
“…Previously published studies have not reached a consensus on gender differences in the perception of NP. Some studies have found that gender is not a predictor of NP (Tanaka, Taketomi, Yonemitsu, & Kawamoto, ; Wynd, ), whereas others have reported that male nurses or male nursing students tend to have higher NP, as in our study (Ko & Kim, ). Ko and Kim () interpreted this result as reasonable, as without a strong perception of NP, males might have found it difficult to choose nursing as a career, despite the social prejudice they would experience.…”
Section: Discussionsupporting
confidence: 42%
“…En la práctica, el significado que cobra el respaldo legal a la función social de la enfermera, y la autonomía profesional, proporcionan la oportunidad para que la profesión se diferencie de otros campos profesionales en cuanto a sus funciones (14,16,17) . Este fortalecimiento organizativo y político respecto al ejercicio liberal de la profesión, la introducción al mercado laboral de sus servicios expertos, la construcción de una identidad, el gobierno y la legislación fueron una expresión de su autonomía.…”
Section: Discussionunclassified
“…[2,3] However, the number of studies using such standardized indices is limited. Tsukakoshi and colleagues [4] and Tanaka, Taketomi, Yonemitsu, and Kawamoto [5] examined staff development and the competencies required in different managerial roles (e.g., nurse leaders, head nurses, and nursing directors). In addition, Hirata [6] explored role perception in managers who had completed Certified Nurse Administrator training.…”
Section: Introductionmentioning
confidence: 99%